Cell surface-based sensing with metallic nanoparticles. (7th July 2015) - Jiang, Ziwen; Le, Ngoc D. B.; Gupta, Akash; Rotello, Vincent M.
<x xml:space="preserve">Abstract</x> Nanoparticles provide versatile platforms for cell-surface sensing for diagnostic and screening applications.